Characterization of protein-enriched yogurt and its effects on the lean body weight gain and electrical activity in skeletal muscle of physically active individuals (Research, Society and Development, 2020)
Protein-enriched yogurts have experienced a growth in marketability in recent years, being demanded especially by consumers interested in increasing their daily apportion of proteins. In this study, the objective was to develop a protein-enriched yogurt and to compare it with a non-enriched yogurt in terms of their physicochemical characteristics, texture, and sensory acceptance after different storage periods and their effects on the lean body weight gain and electrical activity in skeletal muscle of physically active individuals. The supplemented whey protein had a buffering effect on the product, leading to its lower syneresis. Both formulations had similar hardness, indicating that the textural parameters had been retained in the protein-enriched yogurt. Panelists indicated no differences in sensorial attributes between the non-enriched and protein-enriched yogurts, with the sensory characteristics of each product being mainly described by the presence of whey protein and the curdled texture. Consumption of the protein-enriched yogurt did not influence the lean body weight gain by physically active individuals.